Setting the preheating and steady-state operation of electronic ballasts, considering electrodes of hot-cathode fluorescent lamps - Wakabayashi, Fabio Toshiaki; Gomes de Brito, Moacyr Aureliano; Ferreira, Castellane Silva; Canesin, Carlos Alberto (Institute of Electrical and Electronics Engineers (IEEE), 2007)
This paper presents a new methodology for the adjustment of the preheating process and steady-state operation of electronic ballasts intended for hot-cathode fluorescent lamps. The classical series-resonant parallel-loaded half-bridge inverter is the power stage analyzed in this paper. In addition, the preheating process is based on the imposition of a constant rms current through the electrodes, in order to provide a proper value of the R-h/R-c ratio before the lamp start. According to the proposed methodology, it is possible to set suitable operating points for, the electronic ballast, considering optimal conditions for the lamps electrodes. Therefore, the proposed methodology for setting the preheating and steady-state operation is a complete platform to the design of electronic ballasts for hot-cathode fluorescent lamps.
Keywords: electrodes filaments; electronic ballasts; fluorescent lamp model; preheating process; R-h/R-c ratio